Kesan histamin dan glukokotikoid pada sistem surfaktan di paru-paru - Rao, G. Janardhana (1999)
Lecithin, a major surface active substance of surfactant system of the lung was estimated in bronchoalveolar lavage (BAL) fluid in healthy adult male albino rats after administration of hydrocortisone or histamine. BAL was perfomed in three groups of animals following intravenous administration of 2.5 mg. of hydrocortisone sodium succinate at 10 minute, 30 minute and 60 minute intervals respectively. Similarly, BAL fluid was obtained in three groups of animals following subcutaneous administration of 0.06mg of histamine diphosphate at 10 minute, 30 minute and 60 minute intervals. Lecithin content in BAL fluid was estimated by enzymatic method using Boehringer-Mannheim Kits. The results obtained from these animals were compared with those from control animals who received neither hydrocortisone nor histamine. A highly significant reduction in lecithin levels indicating a decrease in surfactant activity was observed within 10 minutes after administration of hydrocortisone or histamine. However, a gradual increase in lecithin levels was observed by one hour in both cases indicating an acute decrease in pulmonary surfactant activity. The effect observed might be due to a sudden inhibition of secretion of pulmonary surfactant by Type II cells or a sudden increase in uptake by Type II cells or both. Further studies are needed to explore the mechanisms involved. Since there is paucity of information on the effect of these substances on surfactant system of lung in adult human being, the findings in the present study clearly indicate a need to assay lecithin content in BAL fluid in patients receiving corticosteroids, as for example, in adult respiratory distress syndrome and bronchial asthma, and, also in patients with allergic disorders such as pulmonary aspergillosis.